POSTULATY ZMIAN W ZIEMSKIM PROCESIE KORONNYM A PRÓBA JEGO REFORMY NA PRZEŁOMIE XVI I XVII WIEKU - Moniuszko, Adam (Zeszyty Prawnicze, 2017)
Po stulates for Changes in Gentry Courts Litigation in the Polish Crown - an Attempt of its Reform on the Turn of the 17th Century Summary A special commission to amend gentry’s law, especially to shorten and simplify the court procedure, was established in 1589. In 1607 the Lvov gentry’s court clerk, one of the commission’s members, Jan Swoszowski introduced his bill of a new court procedure. it was discussed during the diet in 1611, when its author was elected the speaker, and after a debate the am endm ent was decided to be added to the constitutions and sent to the gentry provincial diets. it was opinioned negatively and annulled by parliament in 1613. The gentry also submitted their own numerous proposals applying to the particular changes in litigation. There were three different types of approach to the problem. The first only provided for removal of slight but cumbersome defects. The second demanded some more serious changes but they were put forward in a very general and vague way. The third category of proposals opted for deep changes in those lawsuit procedures which had not worked effectively enough. This diversity of expectations seemed to be one of the main reasons o f the failure of Swoszowski’s bill. Some of the postulates from the first group were enforced during 1607-1609 diets, which might have satisfied a part of the gentry having a more conservative approach. on the other hand Swoszowski’s bill could have offered too little for those who demanded deeper reforms.